Surface reconstruction of La0.95Pr1.05CuO4 as an efficient bifunctional electrocatalyst for water splitting - Altaf, Amna; Sohail, Manzar; Wijayantha, Upul K. G.; Kraev, Igor (Royal Society of Chemistry (RSC), 2026)
The design of a cost-effective, stable, and efficient electrocatalyst for electrochemical water splitting is crucial for hydrogen generation. Non- and compositionally flexible Perovskites are a promising class of catalysts for catalyzing electrochemical water splitting. Herein, we report the synthesis of La0.95Pr1.05CuO4 raw (LPC-R) by the sol–gel method. Then, its surface reconstruction was done by immersing the catalyst in different concentrations of reductive sodium borohydride solution. As a result, an amorphous layer formed on the surface of the catalyst, as observed in scanning electron microscopy (SEM) and High-resolution transmission electron microscopy (HRTEM). The best catalyst, La0.95Pr1.05CuO4 (LPC-2), surface reconstructed by using 2 M sodium borohydride solution, was tested as a bifunctional catalyst and exhibited the lowest overpotential of 260 mV, 104 mV, and Tafel slopes of 54 mV dec−1 and 122 mV dec−1 for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), respectively. Moreover, it also exhibited more than 10 hours of stability. Surface reconstruction tailored electronic structure, and ion stoichiometry form active surface species that contribute to enhancing the catalyst's activity. This work illustrates an efficient strategy of surface reconstruction to improve the performance of as-synthesized catalysts for electrochemical water splitting.
Keywords: 40 Engineering; 3403 Macromolecular and Materials Chemistry; 4016 Materials Engineering; 7 Affordable and Clean Energy; Nanoscience & Nanotechnology; 34 Chemical sciences; 51 Physical sciences